Najlepsze praktyki w analizie finansowej przedsiębiorstwa - Kowalak, Robert (Best Practices in Corporate Financial Analysis, 2007)
The article presents the implementation of best practice in corporate financial analysis. The best practice guarantees the competitive advantage. Properly carried financial analysis (both forward and retrospective) enables to realize strategic and operation purposes - which permit to be active not only in most immediate, but also in more distant future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 233-238